KKN-P: Perancangan Alat Presensi Otomatis dengan menggunakan ID Card Elektronik bagi Pemerintahan Desa Lebakrejo - Suprianto; Kusuma, Dymas Hendra; Lianawati (Journal of Empowerment and Community Service (JECSR), 2024)
Appropriate technology is an innovation designed to provide practical and efficient solutions in various aspects of life in the context of the world of work or education, one of the applications of appropriate technology that is increasingly popular is the use of attendance automation tools. By utilizing various technologies, such as fingerprint, face or card scanning, attendance automation systems not only reduce human error, but also minimize the time required in attendance recording. Appropriate technology research uses qualitative methods that aim to understand the context, process and impact of technology application in society. This method focuses more on collecting descriptive and in-depth data, such as in-depth interviews and group discussions as well as observation and documentation. In addition, this technology also supports transparency, data security, and facilitates attendance management and monitoring. Overall, the application of appropriate technology-based attendance tools is very beneficial in increasing productivity, accountability, and operational efficiency